Defective MnO2 nanosheets based free-standing and high mass loading electrodes for high energy density aqueous zinc ion batteries. (5th October 2021) - Shang, Ping; Liu, Yuanhao; Mei, Yingying; Wu, Lisha; Dong, Yanfeng
Abstract : Defective MnO2 nanosheets based free-standing film electrodes with high mass loadings were constructed for high capacity and high energy density in aqueous and quasi-solid-state zinc ion batteries. Abstract : Aqueous zinc ion batteries (ZIBs) hold great promises for large-scale energy storage and wearable devices due to their low cost and high safety, but suffer from the low capacity and energy density of cathodes for practical applications. Herein, defective MnO2 (d-MnO2 ) nanosheets based free-standing and high mass loading electrodes (H-d-MnO2 ) were successfully developed via an interfacial synthesis of MnO2 nanosheets, phosphorization, and phase inversion procedure combined with a freeze-drying process. Benefiting from the ultrathin thickness of ∼4.2 nm for highly exposed surface with electrolytes, abundant defects ( e.g., oxygen vacancies) in d-MnO2 nanosheets for high capacity and long cycling performance, and porous film electrodes without current collectors for fast ion transfer and high energy density, the d-MnO2 nanosheets loaded on a carbon cloth delivered a high capacity of 241.3 mA h g −1 at 1 C after 250 cycles, superior to MnO2 (84.5 mA h g −1 ). Importantly, the H-d-MnO2 film electrodes exhibited a high specific capacity of 221.4 mA h g −1 at 0.2 C, a high energy density of 265 W h kg −1, and a remarkable initial areal capacity of ∼2.73 mA h cm −2 with an ultrahigh mass loading of 10 mg cm −2 . In addition, the H-d-MnO2 based quasi-solid-state devices were demonstrated to withstand mechanical deformations and power an electronic watch for dozens of hours, suggesting their great potentials in practical applications.